MALDI-based intact spore mass spectrometry of downy and powdery mildews - Chalupová, Jana; Sedlářová, Michaela; Helmel, Michaela; Rehulka, Pavel; Marchetti-Deschmann, Martina; Allmaier, Günter; Sebela, Marek (Journal of mass spectrometry, 2012)
Fast and easy identification of fungal phytopathogens is of great importance in agriculture. In this context, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has emerged as a powerful tool for analyzing microorganisms. This study deals with a methodology for MALDI-TOF MS-based identification of downy and powdery mildews representing obligate biotrophic parasites of crop plants. Experimental approaches for the MS analyses were optimized using Bremia lactucae, cause of lettuce downy mildew, and Oidium neolycopersici, cause of tomato powdery mildew. This involved determining a suitable concentration of spores in the sample, selection of a proper MALDI matrix, looking for the optimal solvent composition, and evaluation of different sample preparation methods. Furthermore, using different MALDI target materials and surfaces (stainless steel vs polymer-based) and applying various conditions for sample exposure to the acidic MALDI matrix system were investigated. The dried droplet method involving solvent evaporation at room temperature was found to be the most suitable for the deposition of spores and MALDI matrix on the target and the subsequent crystallization. The concentration of spore suspension was optimal between 2 and 5 × 10(9) spores per ml. The best peptide/protein profiles (in terms of signal-to-noise ratio and number of peaks) were obtained by combining ferulic and sinapinic acids as a mixed MALDI matrix. A pretreatment of the spore cell wall with hydrolases was successfully introduced prior to MS measurements to obtain more pronounced signals. Finally, a novel procedure was developed for direct mass spectra acquisition from infected plant leaves.
Keywords: Spores, Fungal; spory hub; Plant Leaves; poměr signál - šum; buněčná stěna; houby; Mycological Typing Techniques; Signal-To-Noise Ratio; Cell Wall; kyselina trifluoroctová; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Fungi; Trifluoroacetic Acid; fungální proteiny; mykologické určovací techniky; listy rostlin; Fungal Proteins